Socialization and Debriefing in Educating Mentally Retarded Children: Optimizing Teacher Strategies in Teaching - Syamsul Huda (Smart Society, 2021)
Various strategies that have been used in teaching mental retardation include promoting an emotional approach, thoroughness and strengthening of children's abilities. But in reality, educating mentally retarded children is not easy to accept in teaching. They prefer to play alone and find it difficult to respond to every event and experience what they get. For that we need a strategy in educating so that the teaching and learning system becomes optimal. The purpose of this study was to determine the ability of mentally retarded children to understand PAI subjects. This study uses a qualitative approach, which is a research procedure that produces descriptive data in the form of written or spoken words from people or observed behavior from people (subjects themselves). To obtain data that is as expected, this research uses two methods of data collection, namely interviews and observations. The study has a strategy that needs to be done by teachers, in educating mentally retarded children in PAI subjects, is to use individual learning. This individual learning is considered effective and efficient, considering that mentally retarded students have below average intelligence, as well as their lack of ability in socializing and communicating.